THE EFFECT OF POSITION PROMOTION ON EMPLOYEE SATISFACTION WITH COMPENSATION AS INTERVENING VARIABLES: (Case Study on Harvesting Employees of PT. Karya Hevea Indonesia) - Lasta Irawan, Ari; Briggs, Dana; Muhammad Azami, T.; Nurfaliza, Nurfaliza (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2021)
The results of this study show. (1) It can be seen that the amount of adjusted R square adjusted R square is 0.647 or 64.7%. This shows that compensation (Z) and promotion (X) can explain job satisfaction (Y) by 64.7%, the remaining 35.3% (100% - 64.7%) is explained by other variables outside the research model. this. (2) The results of the t-test (partial) can be seen that the obtained tcount (4.324) > ttable (2.048), as well as the significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the variable of promotion (X) has a positive and significant effect to compensation (Z). (3) The results of the t-test (partial) can be seen that the value of tcount (4.324) > ttable (2.048), as well as the significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the variable of promotion (X) has a positive and significant effect to compensation (Z). (4) The results of the path analysis test show that the direct effect of variable X on variable Y is 0.280. Meanwhile, the indirect effect through the Z variable is -0.011 x -0.289 = 0.0031. From the calculation results obtained, the indirect effect through the Z variable is greater than the direct effect on the Y variable.